Online awareness is associated with superior performance on assessments of functional cognition - Marks, Timothy S.; Giles, Gordon Muir; Edwards, Dorothy Farrar (Frontiers in Aging Neuroscience, 2024)
Background: Intact awareness facilitates an individual's adoption of strategies to support community living skills. However, most studies have not examined awareness during ongoing complex task performance. Objective: To examine whether community-dwelling adult's Accuracy and Strategy use on the Weekly Calendar Planning Activity 17-item version (WCPA-17), Total Cues on the Performance Assessment of Self-care Skills Checkbook Balancing and Shopping Task (PCST), and scores on the self-report Alzheimer's Disease Cooperative Study -Activities of Daily Living Scale (ADCS-ADL) differ between groups who do and do not demonstrate awareness of performance difficulties on the WCPA-17. Methods: Using data collected as part of a larger study we performed a cross-sectional analysis of 274 communitydwelling adults aged 55 to 93 years. Two methods classified participants into groups aware or unaware of their performance. Independent sample t-tests examined group differences on four dependent variables: Accuracy and Strategy use on the WCPA-17, PCST Total Cues, and score on the ADCS-ADL. Results: Using one classification method, aware individuals showed superior Accuracy (p < .001), used more Strategies (p = .002), needed fewer PCST Total Cues (p < .001), and reported greater independence on the ADCS-ADL (p < .004), similar trends were observed with the other method in Accuracy (p < .001) and PCST Total Cues (p < .001) but Strategy use and ADCS-ADL differences failed to reach significance after Bonferroni correction. Conclusions: Groups categorized as aware performed better on all measures. Intact awareness is critical to performance on complex everyday activities and can be evaluated with functional cognition assessments.